IMPROVEMENT OF THE HYDRAULIC EXCAVATOR’S WORKING EQUIPMENT - A. I. Demidenko; I. S. Kuznetsov (Вестник СибАДИ, 2020)
Introduction. The age composition of the main pipelines of Russia significantly exceeds the period of their standard operation, which necessitates the provision of their reliable, trouble-free operation sometimes in difficult environmental conditions. Timely delivery of the required amount of hydrocarbon raw materials to various regions of our country and abroad depends on the quality and speed of the repair work. The speed of the pipeline overhaul, which consists in replacing old pipes with new ones, depends on the effectiveness of the entire repair string as a whole. The main excavation machine is a hydraulic excavator. Soil is removed on both sides of the pipeline, but there is a problem of excavation under the pipeline. Existing solutions to the problem are highly complex, which only complicates the repair process. Therefore, the authors develop the working equipment of the excavator, which is installed after digging the pits of the trench.Materials and methods. The authors performed a review and analysis of existing equipment designs for the soil development under the pipeline. Moreover, the authors developed a new design of interchangeable working equipment for a single-bucket excavator.Results. As a result, the authors presented a detailed description of the working equipment of a single-bucket excavator and the principle of its operation.Discussion and conclusions. The proposed technical solution allows excluding excavation under the main pipeline, which is carried out using a trench tool. This method significantly increases the efficiency of excavation and the pace of repair work as a whole.The authors have read and approved the final manuscript. Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.